Students’ perceptions towards native and non-native english speaker teachers - Ratih Ayu Wulandari; Asih Rosnaningsih; Fairus Sintawati (ETERNAL (English Teaching Journal), 2021)
There was an argument that native English teachers have many advantages than non-native English teachers and students preferred native to non-native teachers; however, the argument had to be assessed. Many researchers had been exploring students’ perceptions of native and non-native English teachers worldwide in formal education institutions. This study aimed to explore students’ perceptions of native and non-native English teachers in a non-formal education institution. This was a qualitative study based on a descriptive approach conducted using three instruments: close-ended questionnaire, semi-structured interview, and documentation. The study revealed that native and non-native English teachers had their own specific roles in the Indonesian context. Students needed native more than non-native teachers because the latter were bilingual having the same mother tongue as them, and they enabled a successful learning process because of the effective learning strategies they shared. Also, non-native teachers helped students deal with difficulties and challenges in their learning process.